Biochemical Estimation of Hemoglobin Livel in protozoan Infected and Treated School Children in Gaza strip - Palestine - F. Alzain, Bassam (مجلة جامعة القدس المفتوحة للبحوث الإنسانية والاجتماعية, 2017)
Two hundred fifty school going children aged (11-17) years old were examined for intestinal parasites. Forty eight (19.2%) children were infected with protozoan parasites (Entamoeba histolytica and Giardia intestinalis). Pretreatment and post-treated blood samples were collected from the same population of the infected children for the estimation of hemoglobin levels. Hemoglobin was estimated using Sahli's hemoglobinometer. Giardia infected female children showed statistical significant difference in the pre and post treatment mean hemoglobin levels. The higher infection rate of commensally strongly suggests the presence of potentially infections and a public health problem. This relationship remained after controlling the range of socio-economic variables. Protozoan infected children were frequently found to have lower blood hemoglobin concentration than uninfected children, but this relationship could not be attributed to protozoan infections alone.